From the s-Process to the i-Process: A New Perspective on the Chemical Enrichment of Extrinsic Stars - Sophie Van Eck; Riano Giribaldi; Thibault Merle; Adrian Lambotte; Drisya Karinkuzhi; Stéphane Goriely; Arthur Choplin; Nicholas Storm; Jeffrey Gerber; Lionel Siess; Maria Bergemann; Alain Jorissen (Galaxies)
Separating stars enriched in the s- and r-processes of nucleosynthesis is usually achieved by analyzing the element ratios of s-process elements (like Ba or La) to r-process elements (like Eu). The situation becomes more complex when analyzing CEMP-rs stars, which are carbon-enriched metal-poor objects enriched in a mixture of s- and r-elements. These objects, possibly resulting from the i-process of nucleosynthesis, are notoriously difficult to classify based on elemental ratios. Recent theoretical studies have outlined, however, that the s-, i-, and r-processes produce distinct isotopic mixtures. Here, we propose to analyze a sample of stars known to be enriched in s, r, or r + s elements and to determine the odd-to-even isotopic ratio measured on atomic lines of barium, in order to validate or disprove their assignation.